PERSEPSI PEDAGANG TERHADAP SISTEM PEMUNGUTAN RETRIBUSI PASAR (STUDI KASUS PADA UPTD PASAR SIMPANG BARU) - Agus Salim; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Implementation of retribution collection system coordinated market is the calculation of the retribution targets, which target the retribution is determined based on the existing potential amount (traders) contained in market Simpang Baru. In addition, the number of compulsory retribution (traders) contained in those markets, which in a market for a compulsory retribution (traders) there are always different numbers every day because at Simpang Pasar Baru is a weekly market, but every day on the market remains there is a trade. In running the system for collection of the retribution markets requires a good planning. Planning is coordinating the activities of which concerns the activities of the work plans that exist in each work unit in accordance with its duties. In connection with it, required each piece of work should draw up a work plan that will be coordinated in the execution of the work to fit the predetermined plan.This research was conducted at the Technical Implementation Unit (UPTD) Simpang Baru Tampan District of the city of Pekanbaru. The purpose of this study was to identify and analyze the perception of traders against the retribution charged market SimpangBaru Pekanbaru, as well as to identify and analyze the factors that influence the perception of traders against the retribution charged market Simpang Baru on Pekanbaru. This research is a qualitative descriptive study, the subjects in this study is a trader at market Baru Simpang sub-district Tampan Pekanbaru, amounting to 156 people. The sampling technique research is simple random sampling technique, the researchers have determined the sample based on the proportion according to the type of merchandise by researchers in accordance with the problems to be studied. Based on the survey results revealed that the perception of traders regarding the management of the market retribution was quite good, especially from the friendly attitude of officers and social relationship that exists between traders with an interpreter collection, while merchant services to meet its own self. Supporting factors in the retribution charged New Simpang market is the creation of a good relationship between officers and traders, the traders concerned and the availability of facilities and infrastructure. The new intersection markets affected by the observance of officers in the rules, obedience traders who occupy the stalls and stalls, as well as the spirit of the officer in carrying out duties and pay dues retribution has an obligation trader. While the retribution charged inhibiting factor is the lack of awareness of some market traders in paying the retribution, less coverage of the object by the officer because of the limited number of polling officers and the magnitude of the market retribution additional tariffs of the market manager.Keywords: Perception, Dealer, Retribution Collection Systems Market, UPTD Simpang Baru.